2016
DOI: 10.3389/fpsyt.2016.00125
|View full text |Cite
|
Sign up to set email alerts
|

A Neural Basis for the Acquired Capability for Suicide

Abstract: The high rate of fatal suicidal behavior (SB) in men is an urgent issue as highlighted in the public eye via news sources and media outlets. In this study, we have attempted to address this issue and understand the neural substrates underlying the gender differences in the rate of fatal SB. The Interpersonal–Psychological Theory of Suicide has proposed an explanation for the seemingly paradoxical relationship between gender and SB, i.e., greater non-fatal suicide attempts by women but higher number of deaths b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 65 publications
0
18
0
1
Order By: Relevance
“…Although the involvement of the insula in STBs has had little direct research focus, its critical involvement in interoceptive processing, detecting salient internal and external stimuli, experiencing emotion, and self-awareness [174][175][176] suggests an important role of the insula in SI. In addition, the insula is implicated in disconnection from bodily experiences, which in turn may lower the threshold to engaging in behaviors that harm the body (in line with the acquired capability theory [177]) thus suggesting a role of the insula in suicide behaviors. In line with important roles of dACC and insula circuitry (as part of the "salience network") in mediating or switching between the extended VMPFC (default mode, affective, reward) systems and the DPFC/IFG (executive control) system [178][179][180], the dACC and insula may represent integral hubs that facilitate the transition from SI to attempt.…”
Section: Discussionmentioning
confidence: 69%
“…Although the involvement of the insula in STBs has had little direct research focus, its critical involvement in interoceptive processing, detecting salient internal and external stimuli, experiencing emotion, and self-awareness [174][175][176] suggests an important role of the insula in SI. In addition, the insula is implicated in disconnection from bodily experiences, which in turn may lower the threshold to engaging in behaviors that harm the body (in line with the acquired capability theory [177]) thus suggesting a role of the insula in suicide behaviors. In line with important roles of dACC and insula circuitry (as part of the "salience network") in mediating or switching between the extended VMPFC (default mode, affective, reward) systems and the DPFC/IFG (executive control) system [178][179][180], the dACC and insula may represent integral hubs that facilitate the transition from SI to attempt.…”
Section: Discussionmentioning
confidence: 69%
“…In addition, schizophrenia patients with a history of suicide attempts showed signi cant volumetric associations with the left middle frontal gyrus [32]. The acquired capability for suicide networks in males consisted of the middle frontal gyrus [33]. A pilot study of differential brain activation to suicidal means and DNA methylation of the CACNA1C gene in SA patients, found that the left middle frontal gyrus was shown to have signi cantly higher brain activation in the SA patients than the controls [34].…”
Section: Discussionmentioning
confidence: 99%
“…Rather, we agree with Campbell and Guiao [41], who claimed that SI as a demonstrative act (carried out in front of others) can entail the intention to induce guilt and shame among close family members in particular. Additionally, lack of fear of death [25] in combination with a sort of copycat effect [11, 12, 33], along with the availability of fluid accelerants and the presence of psychiatric disorders (especially adjustment disorders) may be factors with the potential to deepen our understanding of the psychosocial and psychological conditions favorable to committing suicide by SI.…”
Section: Discussionmentioning
confidence: 99%
“…Further, in a previous study [24] we were able to show that early maladaptive schemas of emotional deprivation, social isolation, shame, and abandonment were related to a history of suicide attempts among patients with major depressive disorders. Additionally, attempting and committing suicide implies behavior-inducing cognitions such as emotional stoicism, sensation-seeking, pain tolerance, and lack of fear of death [25]. …”
Section: Introductionmentioning
confidence: 99%